Diabetes in tuberculosis patients: An emerging public health concern and the determinants and impact on treatment outcome - Sembagamuthu Sembiah; Vivek Nagar; Devendra Gour; Dinesh K Pal; Arun Mitra; Jayeeta Burman (Wolters Kluwer Medknow Publications, 2020)
BACKGROUND: Tuberculosis (TB) and diabetes mellitus are still of much public health concern. Screening of TB patients for diabetes will ensure early case detection, better management of diabetes, and better TB treatment outcome. The objective of this study was to determine the prevalence and associated factors of diabetes in TB patients and their impact on treatment outcome of TB. MATERIALS AND METHODS: This was a longitudinal follow-up study of registered TB patients under the Revised National Tuberculosis Control Program in all five TB units of Bhopal district. Participants were contacted and the interview was conducted. The blood sugar of all TB patients was checked, and they were followed up to assess the treatment outcome from October 2014 to September 2017. Data were analyzed using SPSS (version 16.0. Chicago, SPSS Inc.). Logistic regression was done to find the factors for diabetes in TB patients. The Chi-square tests were used to find the difference in treatment outcomes and assess the relative risk for poor outcome in diabetic TB patients. RESULTS: Of total 662 TB patients, 82 (12.39%) were diagnosed as diabetic. Age >50 years, males, higher body mass index, pulmonary TB, patients on Category II treatment, and history of smoking were found to be predictors of diabetes in TB patients. The treatment outcome of TB was more unfavorable (defaulter, failure, and death) in diabetic TB patients (16.17%) than in nondiabetic TB patients (5.8%) (risk ratio = 2.78, 1.469-5.284 confidence interval). CONCLUSION: The high prevalence of diabetes and the unfavorable treatment outcome in diabetic TB patients make screening and management of diabetes at an early-stage crucial for a better outcome in TB patients.